2009
DOI: 10.2175/193864709793846556
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Characterization of Fresh and Stored Biosolids and Implications of a Screening Level Microbial Risk Assessment

Abstract: A limited study of enteric pathogens from different stages of mesophilic anaerobic digestion (MAD), i.e., primary sludge, and liquid and dewatered (cake) biosolids, was conducted in six wastewater treatment plants (WWTP) in Ontario, Canada. In addition, bacterial pathogens were re-analysed for regrowth after 2 to 3 days storage in a laboratory at 30°C. Pathogen datasets were used in a preliminary screening level quantitative microbial risk assessment (QMRA). The QMRA assumed conservative human health exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The results suggest that sudden increase was less likely to occur with mesophilic processes. Similar observations were reported by Flemming et al (2009), who reported that three out of five mesophilic plants with centrifuge dewatering did not experience increased densities of E. coli or fecal coliform immediately after dewatering. The two plants in that study that did measure greater densities showed an increase of less than one order of magnitude.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results suggest that sudden increase was less likely to occur with mesophilic processes. Similar observations were reported by Flemming et al (2009), who reported that three out of five mesophilic plants with centrifuge dewatering did not experience increased densities of E. coli or fecal coliform immediately after dewatering. The two plants in that study that did measure greater densities showed an increase of less than one order of magnitude.…”
Section: Discussionsupporting
confidence: 89%
“…These results agree with the literature. For example, Flemming et al (2009) reported that five out of five mesophilic digestion processes with centrifuge dewatering experienced increased densities of fecal coliform and E. coli during cake storage compared with one mesophilic process with BFP dewatering, which did not experience regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al (2010) also reported much higher levels of Salmonella in a dewatered biosolids sample than the liquid digested materials (by more than 3 log 10 units). Quantitative microbial risk assessments by Gerba et al (2008) and Flemming et al (2009) have suggested that the potential human health risk posed by direct contact of Salmonella in land applied biosolids was low; however, risks were potentially elevated after regrowth, based on high Salmonella numbers observed in rare cases. Those potential increased risks of infection after regrowth were computed to be ,10 -4 per exposure event after biosolids incorporation into soil (Gerba et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This agrees well with other research. For example, Flemming et al (2009) reported that Salmonella densities in raw sludge ranged from below detection to 3.53 log 10 MPN/g DS, while fecal coliform ranged between 6.3 and 7.9 log 10 MPN/g DS. The difference in the initial densities can be a factor, because first-order kinetics typically are used to describe inactivation rates of bacteria to thermal treatment.…”
Section: Discussionmentioning
confidence: 99%